Swelling Characteristics of Fractal-Textured Bentonite Eroded by Alkaline Solution - Guosheng Xiang; Weimin Ye; Zhijie Hu; Lei Ge; Yinkang Zhou (Advances in Civil Engineering)
To study the swelling characteristics of bentonite eroded by alkaline solutions, swelling deformation (δs) tests on the bentonite subjected to immersion conditions of NaOH and KOH solutions were conducted. It is found that the δs of bentonite decreases with the increase in the concentration of alkaline solution. The swelling deformation δs of bentonite eroded by NaOH solution exceeds than that in the KOH solution for the same level of concentration. Moreover, by performing XRD tests, it is revealed that the reduced swelling performance of bentonite in alkaline solutions is mainly attributed to the dissolution of the swelling mineral, i.e., montmorillonite (Mt.). The higher the concentration of alkali solution, the stronger the dissolution of Mt., thus leading to more significant attenuation of the swelling properties. Besides, the K+ exhibits low hydration energies, which tends to fit into the silicon-oxygen tetrahedral cavity of smectite, forming a stronger K-linkage which leads to closely spaced crystal layers. The e-pe fractal relation can be calculated using the δs of bentonite eroded by alkaline solution. The e-pe fitting relation of the experimental data depicts that the dissolution of Mt. minerals in alkaline solution reduces the swelling coefficient κ, however, it increases the surface fractal dimension (Ds).